2014
DOI: 10.1093/nar/gku510
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of spacer integration intermediates in type I-E CRISPR–Cas system

Abstract: The adaptation against foreign nucleic acids by the CRISPR–Cas system (Clustered Regularly Interspaced Short Palindromic Repeats and CRISPR-associated proteins) depends on the insertion of foreign nucleic acid-derived sequences into the CRISPR array as novel spacers by still unknown mechanism. We identified and characterized in Escherichia coli intermediate states of spacer integration and mapped the integration site at the chromosomal CRISPR array in vivo. The results show that the insertion of new spacers oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 48 publications
5
131
1
1
Order By: Relevance
“…Although this step may be non-essential, it probably enhances the efficiency of the overall process and its specificity toward invading DNA. (2) Selection of DNA fragments for (proto)spacers by scanning for potential PAMs (after partial target unwinding) by one of the four Cas1 subunits of the Cas1-Cas2 complex [63]. (3) Measuring of the selected protospacer generating fragments of the correct size with 3' hydroxyl groups by Cas1 nuclease.…”
Section: Crispr Adaptationmentioning
confidence: 99%
“…Although this step may be non-essential, it probably enhances the efficiency of the overall process and its specificity toward invading DNA. (2) Selection of DNA fragments for (proto)spacers by scanning for potential PAMs (after partial target unwinding) by one of the four Cas1 subunits of the Cas1-Cas2 complex [63]. (3) Measuring of the selected protospacer generating fragments of the correct size with 3' hydroxyl groups by Cas1 nuclease.…”
Section: Crispr Adaptationmentioning
confidence: 99%
“…1A) (7,(18)(19)(20). Cas2 proteins play a critical role in CRISPR adaptation (i.e., the integration of foreign DNA into CRISPR loci) (21)(22)(23)(24)(25), and fusion of the Cas2 adaptation protein to the Cas3 interference protein suggests a functional connection between the two stages of CRISPR immunity. In fact, recent work by Vorontsova et al has shown that new sequence acquisition (both naïve and primed) in type I-F systems requires all of the Cas proteins, including those that were previously thought to be involved exclusively in interference (26).…”
mentioning
confidence: 99%
“…The acquisition module appropriates spacers from foreign DNA into CRISPR arrays and consists of proteins Cas1 and Cas2, homologous in all CRISPR-Cas systems (4). The Cas1 and Cas2 proteins from Escherichia coli alone are able to perform the spacer acquisition reaction in vitro (5) and are also sufficient for spacer acquisition in vivo in the absence of other Cas proteins (6,7). Whenever a new spacer is acquired, a new copy of CRISPR repeat is also generated (1,6).…”
mentioning
confidence: 99%